GH safety workshop position paper: a critical appraisal of recombinant human GH therapy in children and adults. Issue 2 (February 2016) - Allen, D B; Backeljauw, P; Bidlingmaier, M; Biller, B M K; Boguszewski, M; Burman, P; Butler, G; Chihara, K; Christiansen, J; Cianfarani, S; Clayton, P; Clemmons, D; et al.
Abstract : Recombinant human GH (rhGH) has been in use for 30 years, and over that time its safety and efficacy in children and adults has been subject to considerable scrutiny. In 2001, a statement from the GH Research Society (GRS) concluded that 'for approved indications, GH is safe'; however, the statement highlighted a number of areas for on-going surveillance of long-term safety, including cancer risk, impact on glucose homeostasis, and use of high dose pharmacological rhGH treatment. Over the intervening years, there have been a number of publications addressing the safety of rhGH with regard to mortality, cancer and cardiovascular risk, and the need for long-term surveillance of the increasing number of adults who were treated with rhGH in childhood. Against this backdrop of interest in safety, the European Society of Paediatric Endocrinology (ESPE), the GRS, and the Pediatric Endocrine Society (PES) convened a meeting to reappraise the safety of rhGH. The ouput of the meeting is a concise position statement.